DAMPAK SOSIAL EKONOMI INDUSTRI GULA TERHADAP MASYARAKAT: MENINJAU PERAN INDUSTRI GULA DALAM MENINGKATKAN KESEMPATAN KERJA DAN PENDAPATAN MASYARAKAT - Moh Umar; Qaiyim Asy’ari; Muhammad Ali Ja’far; Rb Ahmad Husen Iroki; Rizal Muhaimin; Semi; Rofiqi Ali Tofwan (ICO EDUSHA, 2023)
Abstract: Currently, rural Indonesia is witnessing significant industrial growth. One of them is the Lestari Sugar Factory in the village of Ngrombot, which is located in the Patianrowo district of Nganjuk. The factory is thought to have a positive effect on the economy of the community and can create jobs. The aim of this research is to find out how the existence of sugar factories affects the socio-economic conditions of society. This research uses a qualitative approach and uses case studies as a type of research. The research was conducted in Ngrombot Village, Patianrowo District, Nganjuk District, and the subject was the surrounding community and employees of the company. Data collection methods involve documentation, observations, and interviews. In this study, data analysis includes data minimization, data submission, and conclusion drawings. The results of research on the influence of sugar factories on the socio-economic conditions of the people of Ngrombot village and Patianrowo district of Nganjuk show that the sugar factory has a significant and beneficial impact on the society. This results in a strong family value and improved socio-economic conditions of the family. The existence of industry also led to many business opportunities around the factory. Keywords: Social, Economic, Sugar industry. References Adi. Psikologi Pekerjaan Sosial dan Kesejahteraan Sosial sebagai Dasar Pemikiran. Jakarta: Rajawali Grafindo Persada, 1996. Asy’ari, Musa. Etos Kerja Dan Pemberdayaan Ekonomi Umat. Yogyakarta: Lefti. 1997 Creswell, J. W. (2014). Research Design: Qualitative, Quantitative, and Mixed Methods Approaches (4th ed.). SAGE Publications. Fatikawati, Y. N., & Muktiali, M. (2015). Pengaruh keberadaan industri gula blora terhadap perubahan penggunaan lahan, sosial ekonomi dan lingkungan di Desa Tinapan dan Desa Kedungwungu. Teknik PWK (Perencanaan Wilayah Kota), 4(3), 345-360. Kuncoro, H. (2007). Kausalitas Antara Penerimaan, Belanja, dan PDRB pada Kota dan Kabupaten di Indonesia. Economic Journal of Emerging Markets. Meinarno, Eko A. Manusia Dalam Kebudayaan Masyarakat. Jakarta: Salemba Humanika, 2011. Moleong, Lexy. Metodologi Penelitian Kualitatif. Bandung: PT. Remaja Rosdakarya, 2002. Mulyadi.. Akuntansi Biaya Edisi ke-5. Yogyakarta: BP-STIE YKPN,1993 Nizar, M., Sutamihardja, S., & Suparmoko, S. (2015). Benefit Analysis of Implementation of Alternative SO2 Quality Standards on Acute Respiratory Syndrome (ARI) Incidence Reduction in Indonesia. Makara Journal of Health Research, 135-142. Notoatmodjo, Soekidjo. Pendidikan dan Perilaku Kesehatan. Jakarta: Rineka Cipta, 1993 Soekanto, Soerjono. Sosiologi Suatu Pengantar. Jakarta: PT Raja Grafindo Persada, 2007 Soemarwoto, Otto. Ekologi, Lingkungan Hidup dan Pembangunan. Jakarta: Djambatan Robert, 1997 Undang-undang RI Nomor 5 Tahun 1984 tentang Perindustrian. Republik Indpnesia. Wardhana, R. A., & FERDINAND, A. T. (2012). Analisis Pengaruh Mutu Produk, Reputasi Merek, Dan Promosi Terhadap Minat Beli Konsumen Pada Produk Anti Karat Tuff Kote Dinol (Studi Kasus Pada PT. Sarana Perdana Semarang) (Doctoral dissertation, Fakultas Ekonomika dan Bisnis). Yin. Studi Kasus: Desain dan Metode. Jakarta: Rajagrafindo Persada, 2011